Accountability of Cash Waqf Institutions Post the Implementation of Accounting Standard 412 - Hendra, Grandis Imama; Asnawi, Nur; Ekowati, Vivin Maharani (Share: Jurnal Ekonomi dan Keuangan Islam, 2025)
Indonesia has one of the largest potentials for cash waqf collection in the world due to its majority Muslim population and growing Islamic social finance sector. However, this potential remains largely unrealized, partly due to weak financial transparency and inconsistent reporting practices among waqf institutions. This study aims to assess the level of accountability practices among waqf institutions in Indonesia following the issuance of the Accounting Standard for Waqf (PSAK 412). Data were collected from 432 waqf institutions registered with the Indonesian Waqf Board (BWI), of which only nine institutions had published their 2023 financial statements. Using a content analysis based on PSAK 412 and an accountability index adapted from the Internet Financial Reporting (IFR) model, this study evaluates the extent of compliance and disclosure practices. The findings reveal that most institutions have not yet implemented PSAK 412 adequately. Only three institutions, namely Baitul Maal PLN, Dompet Dhuafa, and Yayasan Wakaf Produktif Pengelola Aset Islami Indonesia (PPAII), demonstrated moderate compliance under PSAK 412, with Baitul Maal PLN achieving the highest overall accountability score and a very high IFR index category. These results emphasize the need for stronger government supervision, socialization, and capacity-building initiatives through BWI to improve waqf accountability and transparency. This study contributes to mapping the post-PSAK 412 accountability landscape and provides a foundation for strengthening governance in Indonesia’s waqf sector. Abstrak Akuntabilitas Lembaga Wakaf Tunai setelah Implementasi PSAK 412. Indonesia memiliki potensi terbesar di dunia dalam penghimpunan wakaf tunai karena mayoritas penduduknya beragama Islam dan sektor keuangan sosial Islam yang terus berkembang. Namun, potensi tersebut belum terealisasi secara optimal akibat lemahnya transparansi keuangan dan praktik pelaporan yang belum seragam di antara lembaga-lembaga wakaf. Penelitian ini bertujuan untuk mengukur tingkat praktik akuntabilitas lembaga wakaf di Indonesia setelah diterbitkannya Pernyataan Standar Akuntansi Keuangan (PSAK) 412 tentang Akuntansi Wakaf. Data diperoleh dari 432 lembaga wakaf yang terdaftar di Badan Wakaf Indonesia (BWI), dengan hanya sembilan lembaga yang mempublikasikan laporan keuangan tahun 2023. Analisis dilakukan menggunakan analisis konten berdasarkan PSAK 412 dan indeks akuntabilitas yang diadaptasi dari model Internet Financial Reporting (IFR). Hasil penelitian menunjukkan bahwa sebagian besar lembaga wakaf belum menerapkan PSAK 412 secara memadai. Hanya tiga lembaga, yaitu Baitul Maal PLN, Dompet Dhuafa, dan Yayasan Wakaf Produktif Pengelola Aset Islami Indonesia (PPAII), yang menunjukkan tingkat kepatuhan menengah, dengan Baitul Maal PLN memperoleh skor akuntabilitas tertinggi dan tergolong dalam kategori sangat tinggi pada indeks IFR. Temuan ini menegaskan pentingnya intervensi, sosialisasi, dan pengawasan pemerintah melalui BWI untuk meningkatkan transparansi dan akuntabilitas pengelolaan wakaf. Penelitian ini berkontribusi dalam memetakan tingkat akuntabilitas pasca penerapan PSAK 412 serta memberikan dasar bagi penguatan tata kelola lembaga wakaf di Indonesia.